2020
DOI: 10.1016/j.lfs.2020.118097
|View full text |Cite
|
Sign up to set email alerts
|

The bio-mission of interleukin-6 in the pathogenesis of COVID-19: A brief look at potential therapeutic tactics

Abstract: Interleukin-6 (IL-6), known as an inflammatory cytokine, can be involved in many innate and adaptive immune responses. The role of IL-6 in the pathogenesis of the novel coronavirus disease 2019 (COVID-19) has recently received much more attention due to the spread of the virus and its pandemic potential. Cytokine storm is among the most critical pathological events in patients affected with coronaviruses (CoVs), i.e., severe acute respiratory syndrome coronavirus (SARS-CoV), Middle East respiratory syndrome co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 140 publications
(149 reference statements)
1
70
0
12
Order By: Relevance
“…Interleukin-6, known to influence osteoclast and osteoblast activity through RANK/RANKL/OPG interactions has been implicated in the cytokine storm associated with ARDS, septic shock, and COVID-19 disease (15)(16)(17).Further, IL-6 is capable of activating nuclear factor kappa-light-chainenhancer of activated B cells (NF-κB) signaling pathways, which can lead to robust innate and adaptive immune response and promote cellular crosstalk between immune and stromal cells. 18 Here we found that LEVs from the plasma of patients with COVID-19 contain key factors involved in regulating IL-6 family signaling, including IL-6, IL-6 RA, OSM, IL-27 and LIF-R. OSM induces IL-6, maintains hematopoietic homeostasis, and, in synergy with TNF and IL-1, also promotes increased cytokine/chemokine expression and tissue destruction (18).While LEV IL-6 levels significantly correlated with both age and LDH, a circulating marker of tissue injury, positive correlation of IL6-RA and negative correlation of LIF-R on LEVs was observed only with LDH levels.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-6, known to influence osteoclast and osteoblast activity through RANK/RANKL/OPG interactions has been implicated in the cytokine storm associated with ARDS, septic shock, and COVID-19 disease (15)(16)(17).Further, IL-6 is capable of activating nuclear factor kappa-light-chainenhancer of activated B cells (NF-κB) signaling pathways, which can lead to robust innate and adaptive immune response and promote cellular crosstalk between immune and stromal cells. 18 Here we found that LEVs from the plasma of patients with COVID-19 contain key factors involved in regulating IL-6 family signaling, including IL-6, IL-6 RA, OSM, IL-27 and LIF-R. OSM induces IL-6, maintains hematopoietic homeostasis, and, in synergy with TNF and IL-1, also promotes increased cytokine/chemokine expression and tissue destruction (18).While LEV IL-6 levels significantly correlated with both age and LDH, a circulating marker of tissue injury, positive correlation of IL6-RA and negative correlation of LIF-R on LEVs was observed only with LDH levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that chloroquine should not be used together with moxifloxacin. The combination of macrolides and fluoroquinolones can prolong QT interval.Cytokine Storm Induced by SARS-CoV-2 and the Drug Therapy methods are shown in Table 2 [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] .…”
Section: Covid-19 May Results In Cardiac Injury Via Several Mechanismsmentioning
confidence: 99%
“… The therapeutic action of hydroxychloroquine can be potentiated by azithromycin, capable of reducing the proinflammatory activity of IL-6 and TNF-α. [61] , [69] , [70] , [72] , [76] , [77] , [84] TNF α TNF-α antagonist:Enbrel,Adalimumab,Etanercept Reduce the infiltration of inflammatory cells (macrophages,neutrophils). The secretion of inflammatory cytokines such as TNF-α, IL-6, IFN-γ and the expression of Toll like receptors (TLR3, TLR4 and TLR7) Down regulate and inhibit the cascade proteins of nuclear factor kappa B (NF-κB, such as MyD88, trif, NF-κ B and p65), Enhance the host's control over virus replication [62] IP10(CXCL10) Nrf2 Activator PB125® Inhibitor cytokine production,induces antioxidant and repair genes [63] , [64] , [71] GCSF, GM-CSF, PDGF, FGF,VEGF Anti-VEGF agents:Bevacizumab Inhibition of vascular leakage [65] , [66] , [67] MCP-1(CCL2),,MIP1α(CCL3), MIP1β, Inhibition of NF-κB activationGlycyrrhizic acid Reducing neutrophil infiltration, inhibiting NF-κB activation and IL-6 formation;inhibiting hepatocyte apoptosis and necrosis.…”
Section: Covid-19 May Results In Cardiac Injury Via Several Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Harnessing this potential of plant-based bioactives to speed up the much-desired development of COVID-19 therapeutics is strengthened by advances in computer-aided drug discovery (CADD) that deploys several computational technologies to the drug design process (Ebhohimen et al, 2020). This computational study identified promising phytochemicals from some of the reported antiviral and anti-inflammatory medicinal plants screened against SARS Cov-2 Nonstructural protein 9 (NSP9) RNA binding protein, and further scrutinizing the probable binding interactions it can have with other targets involved in COVID-19, including the open reading frame protein 3a (ORF3a) which is experimentally found to induce cellular apoptosis (Ren et al, 2020), furin convertase that activates the spike glycoprotein of SARS Cov-2 and interleukin-6, one among the many critical inflammatory cytokines that can significantly contribute to, fever, lymphopenia, coagulation, lung injury, and multi-organ failure (MOF) (Abbasifard et al, 2020). The compounds collected range from chemical classes, including flavonoids, terpenoids, polyphenolics, saponins, thiophenes, furyl compounds, alkaloids, coumarins, sulfides, to polysaccharides.…”
Section: In Silico Virtual Screeningmentioning
confidence: 99%